Komunikasi Guru dalam Pembelajaran Daring pada Anak Berkebutuhan Khusus Tunagrahita - Dinda Yanisya Tifankha; Ike Junita Triwardhani (Bandung Conference Series: Communication Management, 2023)
Abstract. Every human being must communicate for life as well as groups of people who have limitations still do and need special communication. The existence of SLB as a place for children with special needs to develop themselves and get an education. The existence of an online learning system that has just been implemented since the emergence of the Covid-19 virus outbreak has become a new thing that has been implemented by many schools in Indonesia, one of which is SLB BC Nurani. This study aims to find out how teachers communicate in online learning to children with special needs (ABK) with intellectual limitations or are called mentally retarded. This research method is qualitative with a case study approach. Data collection techniques were carried out through interviews, observations, literature reviews and documentation by involving teachers as informants in this study. The results of this study, Interpersonal communication for SLB teachers is important and helps teachers to better understand feelings and in conducting online classes, interpersonal communication is more intensely applied by teachers compared to offline classes. By understanding the characteristics of their students, in online learning the SLB BC Nurani teacher provides support and empathy for mentally retarded students with appreciation, listening to students tell stories, helping students who have difficulties, both verbal and non-verbal. With the support and empathy given, the positive feeling that students receive makes students want to rely on their teacher. There are obstacles that are only encountered during online learning, sourced from communication channels, the environment, the limited distance between teachers and students and parental support. Abstrak. Setiap manusia pasti melakukan komunikasi untuk hidup begitupun golongan orang yang memiliki keterbatasan pun tetap melakukan dan membutuhkan komunikasi secara khusus. Adanya SLB sebagai tempat untuk anak berkebutuhan khusus mengembangkan diri dan mendapat pendidikan. Adanya sistem pembelajaran daring yang baru diterapkan sejak munculnya wabah virus Covid-19 menjadi hal baru yang diterapkan banyak sekolah di Indonesia, salah satunya SLB BC Nurani. Penelitian ini bertujuan untuk mengetahui bagaimana komunikasi guru dalam pembelajaran daring pada anak berkebutuhan khusus (ABK) dengan keterbatasan intelektual atau disebut tunagrahita. Metode penelitian ini yaitu kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data dilakukan melalui Wawancara, Observasi, Tinjauan Pustaka dan dokumentasi dengan melibatkan guru sebagai informan pada penelitian ini. Hasil dari penelitian ini, Komunikasi interpersonal bagi guru SLB merupakan hal yang penting dan membantu guru agar lebih memahami perasaan dan dalam pelaksanaan kelas secara daring, komunikasi interpersonal lebih intens diterapkan oleh guru dibandingkan ketika kelas luring. Dengan memahami karakteristik muridnya, dalam pembelajaran daring guru SLB BC Nurani memberi dukungan dan empati kepada murid tunagrahita dengan apresiasi, mendengarkan murid bercerita, membantu murid yang kesulitan, baik berbentuk verbal ataupun non verbal. Dengan dukungan dan empati yang diberikan, rasa positif yang diterima murid membuat murid mau mengandalkan gurunya. Adanya hambatan-hambatan yang hanya ditemui selama pembelajaran daring, bersumber dari saluran komunikasi, lingkungan, keterbatasan jarak guru dengan murid serta dukungan orang tua.